2019
DOI: 10.1155/2019/5406468
|View full text |Cite|
|
Sign up to set email alerts
|

Spermidine Prevents Heart Injury in Neonatal Rats Exposed to Intrauterine Hypoxia by Inhibiting Oxidative Stress and Mitochondrial Fragmentation

Abstract: Intrauterine hypoxia (IUH) is a common intrauterine dysplasia that can cause programming of the offspring cardiovascular system. In this study, we hypothesized that placental treatment with spermidine (SPD) can prevent heart injury in neonatal offspring exposed to IUH. Pregnant rats were exposed to 21% O2 or 10% O2 (hypoxia) for 7 days prior to term or were exposed to hypoxia and intraperitoneally administered SPD or SPD+difluromethylornithine (DFMO) on gestational days 15-21. Seven-day-old offspring were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 74 publications
1
36
0
Order By: Relevance
“…Ultrathin sections (80-nm-thick) were observed with a JEM-1400 transmission electron microscope (TEM) (Jeol, Tokyo, Japan). Mitochondrial injury was blindly determined by a scoring system, as previous described [19].…”
Section: Methodsmentioning
confidence: 99%
“…Ultrathin sections (80-nm-thick) were observed with a JEM-1400 transmission electron microscope (TEM) (Jeol, Tokyo, Japan). Mitochondrial injury was blindly determined by a scoring system, as previous described [19].…”
Section: Methodsmentioning
confidence: 99%
“…By microarray analysis of human hair follicle mRNA extracts, Ramot et al revealed that SPD can upregulate several key target genes implicated in the control of mitochondrial function [60]. We recently demonstrated that SPD can increase the expression of PGC-1α mRNA in the newborn offspring myocardium exposed to maternal hypoxia [61]. Therefore, the mechanisms underlying SPD-induced mRNA expression changes in signaling molecules of the SIRT1/PGC-1α pathway in the aging myocardium deserve further exploration.…”
Section: Sirt1 Has Been Shown To Increase the Transcriptional Activity Of Pgc-1α By Inducing Its Nuclear Localizationmentioning
confidence: 92%
“…ATP13A2 and its transported substrates have been reported before to protect against conditions of oxidative stress and oxidative stress pathways ( 52 54 ). ATP13A2’s potent antioxidant effect may be key to confer mitochondrial protection to various ROS-inducing neurotoxins such as rotenone, 6-OHDA, and MPP + .…”
Section: Discussionmentioning
confidence: 99%